Financial Performance And Company Value: Good Corporate Governance As Moderation - Setiawati, Channy; Orbaningsih, Dwi; Muawanah, Umi (JAS (Jurnal Akuntansi Syariah), 2024)
This study aims to test and analyze the effect of financial performance on firm value moderated by good corporate governance (GCG) in the banking sector listed on the IDX for 2018-2022. The population in this study was 47 companies in the banking sector. Based on the predetermined criteria, 31 banks were obtained within five years. The data used is secondary data in the form of financial reports from each bank. The data analysis techniques in this study were multiple linear regression and moderated regression analysis using SPSS software. The study results indicate that profitability, liquidity, solvency, and good corporate governance positively affect firm value. Good corporate governance strengthens the relationship between profitability and solvency with firm value. However, good corporate governance weakens the relationship between liquidity and firm value. This study contributes to the literature on the relationship between financial performance and firm value, especially in the banking sector, by showing that good corporate governance can moderate the relationship between profitability, liquidity, and solvency on firm value. This study strengthens the relevance of agency and signaling theories in explaining how good corporate governance can influence market perceptions and investor decisions. This study can reference banks in increasing firm value by considering good corporate governance.